2010
DOI: 10.1124/mol.109.062356
|View full text |Cite
|
Sign up to set email alerts
|

Human Carboxylesterase 1 Stereoselectively Binds the Nerve Agent Cyclosarin and Spontaneously Hydrolyzes the Nerve Agent Sarin

Abstract: Organophosphorus (OP) nerve agents are potent toxins that inhibit cholinesterases and produce a rapid and lethal cholinergic crisis. Development of protein-based therapeutics is being pursued with the goal of preventing nerve agent toxicity and protecting against the long-term side effects of these agents. The drug-metabolizing enzyme human carboxylesterase 1 (hCE1) is a candidate protein-based therapeutic because of its similarity in structure and function to the cholinesterase targets of nerve agent poisonin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 40 publications
2
38
1
Order By: Relevance
“…Thus, we present here for the first time the determination of the bimolecular rate constants for the reaction of pure recombinant human CES1, CES2, and MGL with these oxons. The bimolecular rates of inhibition for CES1 and pesticide oxons reported here are between one and four orders of magnitude higher than those seen for CES1 and nerve agent analogs (sarin, soman, and cyclosarin) (Hemmert et al , 2010). Therefore, CES1 appears to be very efficient at quenching pesticide oxons and is likely a critical enzyme that protects against OP poisoning in humans.…”
Section: Discussioncontrasting
confidence: 53%
“…Thus, we present here for the first time the determination of the bimolecular rate constants for the reaction of pure recombinant human CES1, CES2, and MGL with these oxons. The bimolecular rates of inhibition for CES1 and pesticide oxons reported here are between one and four orders of magnitude higher than those seen for CES1 and nerve agent analogs (sarin, soman, and cyclosarin) (Hemmert et al , 2010). Therefore, CES1 appears to be very efficient at quenching pesticide oxons and is likely a critical enzyme that protects against OP poisoning in humans.…”
Section: Discussioncontrasting
confidence: 53%
“…For example, following determination of the crystal structures of hCE1 in complex with Soman, Tabun or cyclosarin [25, 26], it was observed that substitution of a pair of amino acids (V146H and L363E) might allow a water molecule to act as an intermediate nucleophile to remove the phosphorylated adducts on the serine Oγ atom. Mutagenesis, biochemistry and in vitro kinetic assays confirmed that this could be accomplished, with the greatest activity being observed with cyclosarin [24].…”
Section: Interaction Of Carboxylesterases By Organophosphatesmentioning
confidence: 99%
“…Moreover, development of CES1-based protein therapeutics is being pursued by the Redinbo and Potter groups with the goal of preventing OP nerve agent toxicity and protecting against the long-term side effects of these agents, which could be released on populations in a terrorist attack, during warfare, and following deliberate or accidental exposure to OP agrochemicals. 32 )…”
Section: Role Of Carboxylesterases In Xenobiotic Metabolismmentioning
confidence: 99%